PENGARUH PROMOSI, KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO BANGUNAN CITRA UTAMA - Hartantri Anggita; Ali Ali (Journal of Economic, Bussines and Accounting (COSTING), 2024)
In this day and age, it is necessary to increase the purchase of a product. Consumer purchasing decisions regarding a product need to be considered. The aim of this research is to determine the influence of promotions, product quality and service quality on product purchasing decisions at the Citra Utama Building Store. The population in this research is all consumers who have purchased products at the Citra Utama Building Store. The sample used in this research was 100 respondents. The sampling technique uses probability sampling techniques. Data collection was carried out by respondents filling out existing questionnaires. In this research, structural Equation Modeling (SEM) analysis tools were used, with an emphasis on the Partial Least Squares (PLS) method, and the tool used was Smart PLS version 4.0. Data analysis testing includes checking the Convergent Validity of the Outer Model, Reliability, as well as evaluating the Inner Model which includes R Square, F-Square, and Hypothesis Testing. The results of this research show that promotion and service quality have a positive and significant effect on purchasing decisions at the main image building store. Meanwhile, product quality has no influence on product purchasing decisions at the main image building store.